DNA interaction, cellular localization and cytotoxicity of quinacridone derivatives. (October 2015) - Liu, Ying; Wang, Linlin; Zhou, Jin; Wu, Shangrong; Wei, Yongbiao; Chang, Ang; Liu, Xiangjun; Shangguan, Dihua
Abstract: Quinacridone derivatives (QAs) are widely used in industrial colorant, chemical sensors and organic optoelectronic devices; however their biological applications are rarely reported. Here we describe the interaction of QAs with different DNA forms and cancer cells. Quinacridone and N, N'-bis(5-bromopentyl) quinacridone (QAB) selectively bind parallel G-quadruplex DNA through end-stacking. N, N'-bis(methylpiperazinylpentyl) quinacridone (QAP) and N, N'-bis(dimethyl-aminopentyl) quinacridone (QAT) strongly bind all DNA forms through hydrogen bonding and electrostatic interaction of the alkylamine side chains and DNA. Quinacridone does not enter living cells; QAB enters living cells and mainly locates in lysosome; QAP and QAT enter living cells and locate in whole cells, especially in nuclei through binding DNA. However, these QAs do not show significant cytotoxicity. These results suggest that side chains greatly affect the DNA interaction, cellular permeability and localization of QAs, and provide useful information for the design of DNA-binding drugs and fluorescent probes. Graphical abstract: Highlights: The interaction of quinacridones with different DNA forms was first reported. The interaction of cells with quinacridones was first reported. The side chains on quinacridones greatly affect their interaction with DNA and cells.